Correlation between phosphate level and peritoneal equilibration test (PET) characteristics among continuous ambulatory peritoneal dialysis (CAPD) patients - Ramli, Norazsida (2018)
Hyperphosphatemia is the key abnormality that sets off a cascade of metabolic events in chronic kidney disease (CKD). End stage renal disease (ESRD) patients that undergo Continuous Ambulatory Peritoneal Dialysis (CAPD) uses the peritoneal membrane for solutes filtration and clearance. The differences on the evaluation of peritoneal membrane transport status can affect the rate of toxin removal – serum phosphorus, from the systems. The present study aimed to determine the prevalence of CAPD patients presented with high phosphate level after starting the treatment, to identify the risk factors associated with hyperphosphatemia and to find the significant correlation between the phosphate level and the PET characteristics. A retrospective study was applied for this research where the medical records of patients were reviewed and analyzed between January 2011 to December 2016. Data were collected successfully from 74 adult CAPD patients (41 male, 55.4% and 33 females, 44.6%), with mean age of 51.34 ± 13.75 year-old. In this study, Malays (n= 65, 87.8%) are the largest subjects recruited, while Chinese (n= 6, 8.1%) and Indians (n= 3, 4.1%) made the rest of the subjects. PET characteristics of CAPD patients showed 11 patients had high characteristic (14.9%), 24 high average (32.4%), 26 low average (35.1%) and 5 low (6.8%). There were 37 CAPD patients (50%) presented with high phosphate level after starting the treatment. Simple linear regression revealed that age (p = 0.0052), serum calcium (p = 0.0090), serum albumin (p = 0.0244), normalized protein catabolic rate (nPCR) (p = 0.0126), intact parathyroid hormone (iPTH) (p = 0.0012), total creatinine clearance (p = 0.0470), residual renal creatinine clearance (p = 0.390) and 24-hours urine volume output (p = 0.0060) were risk factors associated with hyperphosphatemia. Pearson’s correlation analysis showed there was no significant correlation between phosphate level and PET characteristics (r = -.232, p = 0.070) while there was significant correlation between PET characteristics and peritoneal solute clearance (r = 0.4748, p < 0.001). In conclusion, serum phosphate level may be associated with daily dietary intake, metabolism and dialysis adequacy. There was no correlation between serum phosphate level and PET characteristic suggesting the rate of the toxin removal might not been affected by the differences on peritoneal membrane characteristics suggesting a further understanding on transport status in terms of its mechanism of toxin removal.